(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2013)
Spanish women were not able to vote until 1931, when they were recognized this right in the Constitution of the Second Republic. This recognition was not easy, because of the opposition of several members of the Constituent Assembly. Some of them wanted to exclude women from politics. Others thought women should be able to vote but not in that moment, because they believed women were not independent enough from priests or their husband or father. Finally, there were those who affirmed that democracy requires participation of women. This one was the opinion of Clara Campoamor, who took part in the writing of the Constitution and, after a great effort, achieved the recognition of the electoral rights of women. In this work, we study how this recognition was get, using the reports of debates in the Constituent Assembly and Clara Campoamor’s writings.